The Effect of Psychological Symptoms on Divergent Thinking in Healthy Older Adults. Issue 3 (3rd July 2021) - Fusi, Giulia; Colombo, Barbara; Zanetti, Marina; Crepaldi, Maura; Rozzini, Luca; Rusconi, Maria Luisa
ABSTRACT: The study of divergent thinking (DT) ability in the elderly population has experienced a renewed interest because of its proven relationship with cognitive reserve (CR). However, experimental research on DT skills in this population has often been inconsistent. One of the reasons why this may have happened is that the possible negative influence of psychological symptoms, which have been proven to be common during older age, have been frequently neglected. Thus, our study aimed at exploring the impact of psychological symptoms (i.e., depression, anxiety, and apathy) on DT abilities in 45 healthy elderly participants (age = 74.2 ± 5.71; 33 women; educational level = 6.51 ± 2.58). The results showed that different psychological symptoms have negative effects on diverse DT indexes: apathetic symptoms correlated negatively with total DT, fluency, and flexibility indexes; depressive symptoms with originality. Moreover, educational level (i.e., a proxy of CR) seemed to have a moderating effect on the relationship between apathy and DT. Even if further studies are needed, future studies should consider the variability of psychological symptoms in the elderly population and their negative effects on different DT indexes and the possible role of CR as a moderator of this relationship. Implications are also discussed.